REKONTEKSTUALISASI MINAT MUZAKKI DI BAZNAS KABUPATEN SUMENEP MELALUI PROFESIONALISME PENGELOLAAN ZAKAT BERBASIS PARTISIPATORIS - Harun AR, Mariatul Qibtiyah; Susanto, Edi (STAIN PAMEKASAN, 2017)
The high potential number of Muzakki in Sumenep needs a well organized management. Additional condition to be done for this empowerment is that the Muzakki, both individually and company, trust their zakat management on the Amil Zakat. The research focusesÂ are: how was the real condition of the potential Muzakki in Sumenep? How is the process of zakat collection, management and distribution in BAZNAS Sumenep? What are the problems faced by BAZNAS Sumenep in order to gain professionalism in managing Zakat? And also how to improve the zakat managerâs skill? The approach used in this study is action research, participatory action research. The object of the study is BAZNAS Sumenep and BAZNAS Karanganyar Solo as the reference which is already successful in terms of professional management. The data collection used are documentation, interview, observation, and Focus group discussion (FGD). The technique of data analysis through 5 steps activity planning, first, making potential local mapping by doing observation to BAZNAS Karanganyar Solo and FGD. Second, conducting Zakat seminar. The third, improving the BAZNASÂ zakat organizerâs skill. Fourth, Social network development. Fifth, assistance, monitoring and evaluating process. The result shows that first, actually it is already potential in sumenep in the process of collecting Zakat, the people of sumenep is religious people who understand their responsibility to pay Zakat. Second, there is no serious attention on the management of Zakat, also on the supporting means. Third, the difficulties faced by BAZNAS Sumenep are the means and infrastructure of the office, the lack of working accountability, the Muzakki did not receive the report of Zakat management, the lack of socialization, support and guidance from local government. Fourth, organizing innovation program of BAZNAS Sumenep by doing some cooperations with SKPD, stakeholders, the board of Amil Zakat, universities and Islamic Boarding House.